Regional-Scale Virtual Nitrogen, Phosphorus, and Potassium Factors of Potato Production in China - Xuejuan Fang; Dongliang Zhong; Weijun Zhou; Mohammad Jawad Alami; Shenghui Cui; Bing Gao; Wei Huang (Agronomy, 2023)
Improving yield in potato production with minimal environmental impact is of great significance for China’s potato staple food policy. Previous research has been limited by the absence of regional-scale parameters to evaluate the environmental costs of regional potato production. To address this gap, we utilized the input–output analysis method to offer a thorough estimation of nitrogen (N), phosphorus (P), and potassium (K) inputs and outputs in the potato production stage at a regional scale, leveraging a meta-analysis dataset from plenty of the literature. On this basis, we calculated the virtual N, P, and K factors (VNFs, VPFs, and VKFs) for different potato production regions, under both conventional and optimal management practices. China’s potato production suffered from excessive N and P inputs, while K inputs remained insufficient. Significant spatial heterogeneities were observed for the VNFs, VPFs, and VKFs across different potato production regions. Northeast China and northwest China emerged as the most suitable potato cultivation regions because they demonstrated high potato yields with relatively low inputs and, consequently, lower VNFs and VPFs. Southwest China was the most vital region where targeted efforts could lead to reducing VNF and VPF, thus significantly mitigating environmental N and P losses. In addition to reducing fertilizer inputs, site-specific and whole optimization measures are proposed to lower the environmental costs and promote the sustainable development of potato production.